2013
DOI: 10.1371/journal.pntd.0002483
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Endemic Chikungunya Virus Infections in Bandung, Indonesia

Abstract: Chikungunya virus (CHIKV) is known to cause sporadic or explosive outbreaks. However, little is known about the endemic transmission of CHIKV. To ascertain the endemic occurrence of CHIKV transmission, we tested blood samples from patients with a non-dengue febrile illness who participated in a prospective cohort study of factory workers in Bandung, Indonesia. From August 2000 to June 2004, and September 2006 to April 2008, 1901 febrile episodes occurred and 231 (12.2%) dengue cases were identified. The remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 37 publications
6
78
1
1
Order By: Relevance
“…On the other hand, the clinical presentation of patients in the present study showed some slightly different features from those seen in African and Asian countries [1][2][3]5,9]. We found the same percentage of fever and arthralgia; however, we observed a lower incidence of myalgia and headache [1,4].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…On the other hand, the clinical presentation of patients in the present study showed some slightly different features from those seen in African and Asian countries [1][2][3]5,9]. We found the same percentage of fever and arthralgia; however, we observed a lower incidence of myalgia and headache [1,4].…”
Section: Discussioncontrasting
confidence: 70%
“…On Reunion Island, severe forms were reported, mainly in patients with underlying medical conditions [4]. These forms included neurological and cardiovascular disorders, hepatitis, skin diseases, and respiratory and renal failure [2,3,5]. Miscarriages and neonatal infections have been also described, and some deaths have been directly attributed to CHIKV [4].…”
Section: Introductionmentioning
confidence: 99%
“…This region is considered as one of the hot spots of emerging viral diseases (Gronvall et al, 2015). The circulation of pathogenic viruses such as Nipah (Lam, 2003;Looi and Chua, 2007), SARS (Goh et al, 2006), H5N1 (Adisasmito et al, 2013), West Nile (Myint et al, 2014), dengue (Sasmono et al, 2015), Chikungunya (Kosasih et al, 2013;Riswari et al, 2016), Zika and coxsackievirus (Wiyatno et al, 2016) has been reported in this region.…”
Section: Pathogenic Viruses Of Biosecurity Concernmentioning
confidence: 99%
“…Sera were collected from factory workers who experienced febrile illnesses during a dengue cohort study in Bandung from 2006-2009 undertaken by Padjadjaran University in collaboration with US-NAMRU#2 [13,14]. In total, 209 sera underwent various testing panels to evaluate the presence of dengue and chikungunya infections.…”
Section: Clinical Specimensmentioning
confidence: 99%
“…Collections were made under institutional review board approvals from the National Institute of Health Research and Development, Indonesian Ministry of Health, and the United States Naval Medical Research Unit No. 2, Jakarta, Indonesia, and written informed consent was obtained as described in the earlier study [13,14]. This follow-up study of archived specimens was reviewed and approved by the ethical committee at the Eijkman Institute for Molecular Biology, Jakarta, Indonesia.…”
Section: Clinical Specimensmentioning
confidence: 99%